2020
DOI: 10.1051/0004-6361/202037942
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO Survey: A new diagnostic for accretion and outflow activity in the young cluster NGC 2264

Abstract: Context. NGC 2264 is a young cluster whose accretion properties can be investigated in detail by taking advantage of the FLAMES data in the context of the Gaia-ESO Survey. In fact, the analysis of the Hα emission line profile can provide us with information about the accretion and ejection activity of young stars. However, a strong nebular emission that contributes to the Hα emission can alter the profiles, with consequences for their physical interpretation. Aims. Our study is aimed at investigating the accre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…G.3-G.13. Some of this variability in the line profile is similar to what has been observed by other authors (e.g., Jayawardhana et al 2006;Biazzo et al 2012;Fang et al 2013;Sousa et al 2016;Bonito et al 2020). A detailed analysis of the kinematic variations traced by the shape of the emission lines, as well as by the profiles of the forbidden lines, will be subject of future works.…”
Section: Variability From High-resolution Spectrasupporting
confidence: 84%
“…G.3-G.13. Some of this variability in the line profile is similar to what has been observed by other authors (e.g., Jayawardhana et al 2006;Biazzo et al 2012;Fang et al 2013;Sousa et al 2016;Bonito et al 2020). A detailed analysis of the kinematic variations traced by the shape of the emission lines, as well as by the profiles of the forbidden lines, will be subject of future works.…”
Section: Variability From High-resolution Spectrasupporting
confidence: 84%
“…The older ages inferred from magnetic models have obvious implications for the empirical estimation of timescales associated with the evolution of PMS stars and their circumstellar environments, which are usually calibrated using groups of stars with assigned isochronal ages. These include the timescales associated with accretion processes for the youngest clusters (Bonito et al 2020), the lifetimes of protoplanetary disks (Carpenter et al 2006;Ribas et al 2015;Li & Xiao 2016) dissipation rates of debris disks (Binks & Jeffries 2017;Silverberg et al 2020) and the angular momentum evolution for Solar-type and low-mass stars in clusters (Gallet & Bouvier 2013;Amard et al 2019). The clusters studied in this work are at the forefront of near-future exoplanet surveys (Kastner et al 2019), allowing astronomers to empirically test models of planetary formation and evolution in the first ∼ 100 Myr.…”
Section: Implications For Stellar Modelsmentioning
confidence: 95%
“…It provides stellar parameters, metallicity, and elemental abundances, radial velocities, and additional products, such as gravity index, chromospheric activity tracers, mass accretion rate diagnostics, and veiling. Several works in recent years have been devoted to the study of open clusters observed by the GES, among many we recall the latest ones: Bertelli Motta et al [76], Magrini et al [77,78,79], Prisinzano et al [80], Hatzidimitriou et al [81], Casali et al [82,83], Baratella et al [84], Randich et al [85], Jackson et al [86], Bonito et al [87], Gutiérrez Albarrán et al [88], Semenova et al [89], Binks et al [90]. In the following sections, we adopt the average abundances from IDR6 for the member stars of 57 clusters with ages ≥ 120 Myr published in Magrini et al [79].…”
Section: Gaia-esomentioning
confidence: 99%